The effectiveness of the physical education curriculum following the Sports Club model on the physical development of high school students in Vietnam - Tu Tran; Cuong Do; Tien Ha (IP Iermakov S.S., 2024)
Background and Study Aim. The physical development of high school students is often hindered by the limitations of traditional physical education programs, which may not fully engage students or promote balanced physical growth. In light of these concerns, the need to explore alternative educational models that can enhance students' physical development has become evident. The purpose of this article is to evaluate the potential effectiveness of a physical education curriculum following the Sports Club model in improving the physical development of high school students. Material and Methods. A total of 84 female 10th-grade students participated in the study. They were divided into two groups: an experimental group of 42 students following the Sports Club model and a control group of 42 students following the current physical education curriculum. The experiment lasted for 17 weeks. Both groups completed initial and final physical fitness tests. These tests included the 30-second sit-up test (to assess core strength), the 30-meter sprint test (to measure speed), the 4 × 10-meter shuttle run test (to evaluate agility), the standing long jump test (to measure explosive leg power), and the 5-minute running field test (to assess endurance). Results. The female students in the experimental group demonstrated greater physical development compared to the control group in all five assessment tests. The experimental group showed the most significant improvement in the 30-second sit-up test, with a growth rate of 26.71%. The lowest growth was observed in the 5-minute running field test, at 9.92%. In contrast, the control group showed its highest improvement in the 30-second sit-up test, with a growth rate of 9.44%. However, there was minimal to no improvement in the 4 × 10-meter shuttle run and the 5-minute running field test for the control group. Conclusions. The Sports Club model improved students' physical fitness more effectively compared to the current curriculum, offering greater benefits in all tested areas. It is recommended that teachers further integrate and refine the implementation of the Sports Club model in future physical education programs to enhance teaching effectiveness.